Attitudes Towards Homosexuality and Women in Male-Authored Writing: An analysis of Zijin Chen’s Detective Fiction - Aiqing Wang (Lingua Didaktika: Jurnal Bahasa dan Pembelajaran Bahasa, 2023)
Zijin Chen, ‘the Chinese Keigo Higashino’, is celebrated for reality-oriented detective fiction addressing social issues. Notwithstanding phenomenal screen adaptation, his chef-d’oeuvre The Long Night, along with a series entitled To Murder Government Officials manifest his conspicuous stances pertaining to homosexuality and women. To be more specific, characters in his narratives are prone to regard homosexual men and relationships with disdain, and exhibit the male gaze and gender stereotypes of women. Although the mentality is not necessarily triggered by homophobia or misogyny, the author might have been impinged upon by outdated policies and stigma and hence is featured by lack of feminist awareness.